Wybrane rozwiązania strukturalne stosowane w procesie sekurytyzacji aktywów - Kalasińska, Magdalena (Selected Structural Solutions Applied to the Securitization of Assets, 2005)
Since first processes of securitization have been conducted, the number of investors, and also forms and methods applied, increased. A range of assets and structural solutions used in securitization have accordingly increased. The appropriate finance structures and securities issued in course of securitization are matched with regard to e large variety of assets. It appears that the properties of these assets determine the financial structure of securitization and the Asset Backed Securities characteristics. Therefore, companies apply different solutions to short-term and long-term assets securitization. The paper presents some selected financial structures which can be used in securitization. It also aimes at showing that the right choice of financial structures in securitization has an effect on the achievement of its goals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 164-173